Aurora-a Kinase: A Novel Target of Cellular Immunotherapy for Human Leukemia - Ochi, Toshiki; Fujiwara, Hiroshi; Suemori, Koichiro; Azuma, Taichi; Kuzushima, Kiyotaka; Yasukawa, Masaki (Blood, 2008)
[Purpose] Aurora-A kinase (Aur-A) is a member of the serine/threonine kinase family, and the Aur-A gene is located at chromosome 20q13. Aur-A is mainly expressed in the G2/M phase of the cell cycle and regulates mitotic cell division in normal cells. Aur-A is expressed exclusively in testis in normal tissues, but is abundantly expressed in various kinds of cancer including hematological malignancies. Its overexpression usually accompanies chromosomal abnormality related with the poor prognosis. Furthermore, the silencing of Aur-A gene has disrupted the proliferation of cancer cells and augmented their susceptibility to anti-cancer agents. These data strongly suggest that Aur-A is one of the crucial oncognes and a rational target for cancer treatment. Thus, we postulated that Aur-A might be an ideal target for cancer immunotherapy, and attempted to verify the feasibility of cellular immunotherapy for leukemia targeting Aur-A. [Methods] Nine-mer peptides derived from Aur-A which were algorithmically predicted to bind to HLA-A*0201 molecule were synthesized and assessed their binding affinities by the stabilization assay with T2 (HLA-A*0201) cells. Aur-A-specific cytotoxic T lymphocytes (CTLs) were generated by stimulation of CD8+ T cells with Aur-A peptide-pulsed autologous dendritic cells. Cytotoxicity of Aur-A-specific CTLs was defined by standard 51Cr-release assay. HLA class I restriction was examined with anti-HLA class I antibody and target-specificity of Aur-A-specific CTLs was examined by cold target inhibition assay with 51Cr-labeled HLA-A*0201-positive leukemia cell lines in combination with Aur-A peptide-loaded 51Cr-unlabeled HLA-A*0201-positive lymphoblastoid cell lines. The expressions of Aur-A mRNA and Aur-A protein in leukemia cells and normal cells were assessed by semi-quantitative real-time PCR and Western blotting. The frequencies of Aur-A-specific CTL precursors in the peripheral blood of healthy individuals and patients with leukemia were measured by tetramer staining. [Results] We established an HLAA* 0201-restricted and Aur-A207-215 peptide (YLILEYAPL)-specific CTL line (designated as AUR-1) by repeated stimulations of CD8+ T cells with Aur-A207-215 peptide-pulsed peripheral blood mononuclear cells from an HLA-A*0201-positive healthy individual. AUR-1 exerted cytotoxicity to various kinds of leukemia cell lines in an HLA-A*0201- restricted fashion. AUR-1 could discriminate freshly isolated leukemia cells from normal cells and normal mitotic cells, according to the expression levels of Aur-A mRNA. By using freshly isolated leukemia cells from CML patients' bone marrow mononuclear cells (BMMCs), we further investigated whether AUR-1 could lyse the leukemic progenitor cells. The CD34+CD38low fraction of CML BMMCs which include leukemic stem cells but not the normal counter part cells overexpressed Aur-A mRNA. Additionally AUR-1 could lyse CD34+ CML BMMCs, but not normal CD34+ cells. Finally, by using tetramer assay, Aur-A207-215-specific CTL precursors were detected more frequently in the peripheral blood of HLA-A*0201-positive patients with leukemia than that of healthy individuals. [Conclusion] This is the first report that Aur-A-specific CTLs can exert the cytotoxicity against leukemic stem cells but not normal hematopoietic stem cells. Results in this study suggests that the cellular immunotherapy targeting Aur-A is a promising strategy for the treatment of human leukemia.